SIMULATION OF THE EFFECT OF DEE RADIUS ON THE KINETIC ENERGY OF A CYCLOTRON ACCELERATOR USING PYTHON PROGRAMMING AS A STUDY OF PROTON THERAPY - Muhammad Za’im; Cindy Salsadila (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Cancer is a dangerous disease and one of the leading causes of death worldwide. One of the treatments for cancer is radiotherapy. Proton radiotherapy has been widely developed due to its advantage of reducing damage to healthy tissue surrounding the cancer. The source of proton radiotherapy comes from an accelerator, and currently, the most commonly developed type is the cyclotron. This study aims to simulate and analyze the effect of the dee radius on the kinetic energy produced by the cyclotron. The research was conducted using an in silico method with the Python programming language. Based on the simulation results, the kinetic energy produced by the cyclotron for dees radii of 0.2 m, 0.25 m, 0.3 m, 0.35 m, and 0.4 m are 1.644 MeV, 2.639 MeV, 3.941 MeV, 5.462 MeV, and 7.246 MeV, respectively. Therefore, the larger the dee radius used, the greater the kinetic energy of the proton produced. This occurs because a larger dee radius allows the proton to pass through the gap between the dees more frequently. When the proton crosses the gap between the dees, its velocity increases due to acceleration caused by the potential difference between the two dees, resulting in higher kinetic energy.